(untitled) (ASEAN Engineering Journal, 2014)
Heavy metals in suspended sediments (SS) were investigated in the lower Chao Phraya River, Thailand, and Marikina-Pasig River basin, Philippines, both in the rainy and dry seasons. In addition, we assessed the relative pollution level of SS by determining enrichment factor of particulate metals. The particulate fractions accounted mostly for 60-100% of total concentrations of Cr, Mn, Ni, Cu, Zn, and Pb in both dry and rainy seasons. The comparison of metal contents of the sampled SS and upper continental crust (UCC) implied some anthropogenic inputs of Cr, Ni, Cu, and Zn as well as the dilution process for those metals in the rainy season in Chao Phraya River. Enrichment factor in both rivers also indicated anthropogenic effects on metal content in SS, reflecting the distinctive seasonal process in Chao Phraya River and the spatial variation within Marikina-Pasig River basin. Overall, the results revealed the importance of the particulate phase of heavy metals in both target rivers to understand the transport and reactivity of heavy metals.